Polyimide binder for positive electrode of lithium ion battery and preparation method of polyimide binder
By using polyimide binder, inclusion of cyclodextrin and introduction of sulfonate groups, the shortcomings of existing lithium-ion battery binders in terms of energy density, cost and safety are solved, and the battery electricity is significantly improved Chemical properties and cyclic stability.
Patent Information
- Application Number
- CN202411511417.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Existing lithium-ion batteries have shortcomings in terms of energy density, cost and safety, especially polyvinylidene fluoride (PVDF) as a binder, which has poor flexibility, swelling and safety risks.
Polyimide is used as the binder to enhance the conduction speed and efficiency of lithium ions in electrode materials by incorporating cyclodextrin and introducing groups such as sulfonate, thereby enhancing the adhesion and electrochemical properties.
It improves the rate performance and energy density of lithium-ion batteries, reduces electrode impedance, enhances the flexibility and cycle stability of the electrode sheet, and improves the overall electrochemical performance of the battery.
Smart Images

Figure CN119391360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof. Background Art
[0002] As a new generation of green energy storage system, lithium-ion batteries have the advantages of high specific energy, high energy density, high coulombic efficiency, high operating voltage, long cycle life, and wide operating temperature range. Therefore, lithium-ion batteries are widely used in portable electronic products, electric vehicles and other fields, but their application in these fields still has problems such as energy density, cost, and safety. The development of high energy density, low cost and high safety lithium-ion batteries is still the focus of current research.
[0003] Lithium-ion batteries are composed of components such as positive electrodes, separators, electrolytes and negative electrodes. The positive and negative electrodes are composed of powdered active materials (such as lithium metal oxides, carbon negative electrode materials), conductive agents, electrode current collectors and binders. The role of the binder is to bind the active materials, conductive agents and current collectors together. For an ideal electrode, each active particle should be reasonably shaped, dispersed and connected to the current collector and electrolyte, with low resistance and continuous internal channels.
[0004] For a long time, in the large-scale production of lithium-ion batteries, polyvinylidene fluoride (PVDF) has been mainly used as a binder and organic solvent N-methylpyrrolidone (NMP) as a dispersant. However, PVDF has its own shortcomings, such as poor flexibility and bonding performance, a certain amount of swelling in the electrolyte, and strong adhesion to metal lithium and Li x C6 undergoes an exothermic reaction at relatively high temperatures, posing a significant safety hazard.
[0005] Therefore, in view of the above problems, the present invention provides a polyimide binder for lithium ion battery positive electrode and a preparation method thereof. There are multiple hydroxyl groups (-OH) in the molecular structure of cyclodextrin, and these hydroxyl groups can form hydrogen bonds and other physical and chemical interactions with the surface of the electrode material, thereby providing good bonding force. The molecular structure of cyclodextrin has the characteristics of being hydrophilic inside and hydrophobic outside, and it can promote the penetration of electrolyte and ion migration through its internal pore structure. This characteristic helps to improve the conduction speed and efficiency of lithium ions in the electrode material during the charge and discharge process, thereby improving the rate performance and energy density of the battery. The sulfonate group can dissociate the negatively charged sulfonate ion, increase the ionic conductivity in the electrode, and improve the transmission efficiency of lithium ions in the electrode, thereby improving the overall electrochemical performance of the battery. Polyimide materials have the characteristics of structural diversity, good thermal stability, stable chemical structure, excellent mechanical properties, etc. As a binder in the positive electrode of a lithium ion battery, it is of great significance to the development of polyimide with high capacity, stable cycle performance and good safety performance. Summary of the invention
[0006] The invention aims to provide a polyimide binder for lithium ion battery positive electrode and a preparation method thereof, wherein the binder has the advantages of excellent thermal stability, stable chemical structure and strong bonding force. The binder improves the conduction speed and efficiency of lithium ions in electrode materials by including cyclodextrin and introducing groups such as sulfonate, thereby improving the rate performance and energy density of the battery, reducing the electrode impedance, increasing the flexibility of the pole piece, and ensuring the cycle stability of the lithium ion battery.
[0007] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0008] A polyimide binder for a lithium ion battery positive electrode, the polyimide binder for a lithium ion battery positive electrode comprising a polyimide containing cyclodextrin and a sulfonic acid group, the polyimide structural formula is shown in structural formula 1:
[0009]
[0010] Wherein, m is any integer from 100 to 1000, and the weight average molecular weight is greater than 20000.
[0011] Preferably, the group A in the structural formula 1 is selected from any one of the following structural formulas:
[0012]
[0013]
[0014] Preferably, the B group in the structural formula 1 is selected from any one of the following structural formulas:
[0015]
[0016] The present application also claims a method for preparing a polyimide binder for a lithium ion battery positive electrode, comprising the following steps:
[0017] (1) Under nitrogen protection, cyclodextrin, sulfonated diamine and triethylamine are dissolved in an organic solvent, stirred until fully dissolved, and then dibasic acid anhydride is added, and stirred at 60-100° C. for 6-12 hours to obtain a solution containing sulfonated polyamic acid included in cyclodextrin;
[0018] (2) Add benzoic acid and a catalyst to the solution of sulfonated polyamic acid encapsulated by cyclodextrin obtained in step (1), raise the temperature to 180-220° C., react at a constant temperature for 10-18 hours, perform imidization, cool to room temperature, add a washing solvent to precipitate, filter, and obtain the polyimide binder for the positive electrode of a lithium ion battery.
[0019] Preferably, in step (1), the molar ratio of the cyclodextrin to the sulfonated diamine is 1:0.5-1.5; the molar ratio of the sulfonic acid group in the sulfonated diamine to triethylamine is 1:0.9-1.1;
[0020] The cyclodextrin is selected from one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin;
[0021] The organic solvent is selected from one or a mixture of two or more of m-cresol, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, and p-chlorophenol;
[0022] The solid content of the sulfonated polyamic acid solution is 10-25 wt %.
[0023] Preferably, in step (2), the washing solvent is selected from one or more of ethyl acetate, methanol, ethanol, isopropanol, ethylene glycol, 2-butanol or cyclopentanol;
[0024] The catalyst is selected from one of quinoline, isoquinoline or tertiary amine.
[0025] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0026] S1, taking a polyimide binder and stirring it to dissolve it in a solvent to obtain a binder solution, grinding and mixing the positive electrode active material and the conductive agent, and then adding them to the binder solution, and adjusting the viscosity of the mixed material to 2000-10000 mPa·s by adding a solvent to obtain a black slurry;
[0027] S2. The black slurry obtained in step S1 is evenly coated on aluminum foil, and compacted after drying to obtain a positive electrode sheet for a lithium-ion battery.
[0028] Preferably, in step S1, the solvent is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone;
[0029] The positive electrode active material is selected from one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide or ternary positive electrode material nickel cobalt manganese oxide;
[0030] The conductive agent is selected from one or more of acetylene black, superconducting carbon black Super P, carbon nanotubes, graphene and Ketjen black.
[0031] Preferably, in step S1, the mass concentration of the binder solution is 5%-20%; in step S2, the drying is vacuum drying at 80°C-120°C.
[0032] Preferably, in step S1, the positive electrode active material content is 2 mg·cm-2 -4mg cm -2 ; In step S2, the positive electrode plate of the lithium-ion battery is composed of an active material layer and an aluminum foil; the active material layer is composed of a positive electrode active substance, a conductive agent and a polyimide binder; the mass content of the binder in the active material layer is 1%-15%; the mass content of the conductive agent in the active material layer is 2%-25%.
[0033] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0034] 1. The polyimide binder for the positive electrode of the lithium ion battery of the present invention has polyimide as the skeleton, has excellent thermal stability, strong mechanical properties, improves the bonding strength of the binder, and effectively inhibits the separation between the binder and the active material particles and the aluminum foil;
[0035] 2. The polyimide binder for the positive electrode of the lithium ion battery of the present invention includes cyclodextrin on the polyimide backbone chain. The molecular structure of cyclodextrin contains multiple hydroxyl groups, which can form hydrogen bonds and other interactions with the surface of the electrode material to provide good bonding force; the internal pore structure of cyclodextrin can also promote the penetration of electrolyte and ion migration, thereby improving the cycle performance;
[0036] 3. The polyimide binder for the positive electrode of the lithium ion battery of the present invention introduces sulfonate groups and the like, which can dissociate sulfonate ions with negative charges, increase the ionic conductivity in the electrode, and improve the transmission efficiency of lithium ions in the electrode;
[0037] 4. The electrode sheet prepared by the polyimide binder of the present invention is used in lithium-ion batteries, which effectively enhances the electrochemical performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, some of the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 This is a schematic diagram of the battery assembly process of Example 1 of the present invention;
[0040] Figure 2 This is a schematic diagram of the structure of a battery positive electrode prepared in Example 1 of the present invention;
[0041] Figure 3 This is a SEM image of the initial morphology of the electrode piece of the battery positive electrode prepared in Comparative Example 1 of the present invention, with a magnification of 1000 times;
[0042] Figure 4 This is a SEM image of the initial morphology of the electrode piece of the battery positive electrode prepared in Example 1 of the present invention, with a magnification of 500 times;
[0043] Figure 5 The bonding strength curve diagram of the electrode sheet of the positive electrode of the battery prepared in Example 1 of the present invention and Comparative Example 1;
[0044] Figure 6 The initial impedance diagram of the assembled battery of Comparative Example 1 of the present invention and the impedance diagram after 100 cycles;
[0045] Figure 7 The cycle performance diagram of the assembled batteries of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0046] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0047] The present invention is further described below in conjunction with the examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0048] Example 1
[0049] See attached Figure 1 , Attachment Figure 2 , Attachment Figure 4 , Attachment Figure 5 And attached Figure 7 This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0050] (1) Under nitrogen protection, 1.794 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3-sulfonic acid, 4.54 g of β-cyclodextrin and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, stirred until fully dissolved, and then 1.2533 g of 4,4'-oxydiphthalic anhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid included in cyclodextrin;
[0051] (2) adding 0.0844 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at a constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0052] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0053] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0054] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0055] Example 2
[0056] This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0057] (1) Under nitrogen protection, 1.794 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3-sulfonic acid, 4.54 g of β-cyclodextrin and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, stirred until fully dissolved, and then 1.3018 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid included in cyclodextrin;
[0058] (2) adding 0.0849 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at a constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0059] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0060] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0061] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0062] Example 3
[0063] This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0064] (1) Under nitrogen protection, 1.794 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3-sulfonic acid, 4.54 g of β-cyclodextrin and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, and stirred until completely dissolved. Then, 2.1028 g of bisphenol A diether dianhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid included in cyclodextrin;
[0065] (2) adding 0.0929 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0066] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0067] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0068] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0069] Example 4
[0070] This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0071] (1) Under nitrogen protection, 2.1142 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3,3'-disulfonic acid, 4.54 g of β-cyclodextrin and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, and stirred until completely dissolved. Then, 1.2533 g of 4,4'-oxydiphthalic anhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid encapsulated by cyclodextrin;
[0072] (2) adding 0.0876 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0073] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0074] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0075] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0076] Example 5
[0077] This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0078] (1) Under nitrogen protection, 2.1142 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3,3'-disulfonic acid, 4.54 g of β-cyclodextrin and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, and stirred until completely dissolved. Then, 1.3018 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid encapsulated by cyclodextrin;
[0079] (2) adding 0.0881 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0080] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0081] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0082] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0083] Example 6
[0084] This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0085] (1) Under nitrogen protection, 2.1142 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3,3'-disulfonic acid, 4.54 g of β-cyclodextrin and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, and stirred until completely dissolved. Then, 2.1028 g of bisphenol A diether dianhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid included in cyclodextrin;
[0086] (2) adding 0.0961 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0087] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0088] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0089] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0090] Comparative Example 1
[0091] See attached Figure 3 , Attachment Figure 5 , Attachment Figure 6 And attached Figure 7 This embodiment provides a method for preparing a positive electrode sheet of a lithium-ion battery, comprising the following steps:
[0092] S1, take 0.1g polyvinylidene fluoride (PVDF) and dissolve it in 2.0ml N-methylpyrrolidone to obtain a binder solution, take 0.8g lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0093] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0094] Comparative Example 2
[0095] See attached Figure 7 This embodiment provides a polyimide binder for a lithium ion battery positive electrode and a preparation method thereof, comprising the following steps:
[0096] (1) Under nitrogen protection, 1.794 g of 4,4'-di(4-aminophenoxy)-[1,1'-biphenyl]-3-sulfonic acid and 0.85 g of triethylamine were dissolved in 20 ml of m-cresol, and stirred until completely dissolved. Then, 1.2533 g of 4,4'-oxydiphthalic anhydride was added, and stirred at 80° C. for 8 h to obtain a solution containing sulfonated polyamic acid encapsulated by cyclodextrin;
[0097] (2) adding 0.039 g of isoquinoline and 0.7327 g of benzoic acid to the sulfonated polyamic acid solution containing cyclodextrin included in step (1), heating to 180° C., reacting at constant temperature for 18 h, and performing imidization. After the reaction is completed, cooling to room temperature, dripping ethyl acetate into the polyimide solution to precipitate, filtering, and obtaining the polyimide binder for the positive electrode of the lithium ion battery;
[0098] The method for preparing the lithium ion battery positive electrode sheet using the polyimide binder for the lithium ion battery positive electrode comprises the following steps:
[0099] S1, take 0.1g of the binder and dissolve it in 1.5ml N-methylpyrrolidone to obtain a binder solution, take 0.8g of lithium cobalt oxide (LiCoO2) positive electrode active material and 0.1g of conductive agent Super P, grind and mix them thoroughly, add them to the binder solution in batches, and stir to mix them evenly to obtain a black slurry;
[0100] S2. Use a four-sided preparation device to evenly coat the black slurry obtained in step S1 on a clean aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a LiCoO2 lithium-ion battery positive electrode sheet.
[0101] The positive electrode sheets of the lithium-ion batteries obtained in the above-mentioned embodiments and comparative examples were cut into round sheets with a diameter of 14 mm, rolled, weighed and tested. The test results are shown in Table 1.
[0102] The positive electrode sheets of the lithium-ion batteries obtained in the above examples and comparative examples were tested as follows:
[0103] The positive electrode sheet was dried and weighed and then put into the glove box, and the button battery was assembled with a 2032-type button battery shell: the positive electrode shell, positive electrode sheet, diaphragm, lithium sheet, gasket, and spring were placed in order, 60 μL of electrolyte was added, the positive electrode shell was covered, and the button battery was sealed on a sealing machine; the electrode sheet preparation and battery assembly are applicable to all embodiments and comparative examples;
[0104] Electrochemical long cycle test: The battery test system of Blue Electric Electronics Co., Ltd. was used to test the battery cycle performance at room temperature (25°C). First, 3 cycles were performed, and then a long cycle test was performed at a current density of 0.5C. The test voltage range was 2.5-4.5V.
[0105] AC impedance test: battery test conditions, amplitude is 1mV, frequency range is 10 -2 -10 6 Hz, the initial interfacial impedance of the test battery and the interfacial impedance after 100 cycles;
[0106] Adhesion strength test: Cut the prepared and completely dried positive electrode into strips of 25mm wide and 150mm long; then stick one side of the 3M double-sided tape on a clean aluminum plate, smooth it with force to ensure that the double-sided tape is tightly attached to the aluminum plate, peel off the double-sided tape, and stick one side of the electrode coated with the slurry on the tape, and make sure that the electrode and the double-sided tape are matched and fitted; insert the aluminum plate with the fixed electrode into the lower clamp and fix it vertically; insert the un-adhesive electrode into the upper clamp and fix it, so that the electrode attached to the double-sided tape is 180° with the electrode fixed by the upper clamp. After fixing the test sample, first calibrate and reset it, the peeling speed is 100mm / min, and then start the test to get the peel strength curve and average value.
[0107] Table 1
[0108]
[0109] As can be seen from Table 1, the average bonding strength of Examples 1-6 is higher than that of Comparative Example 1, which shows that the polyimide binder used in the present invention has a strong bonding force with the pole piece, and there is a strong interaction between the polyimide and the positive electrode component, which effectively inhibits the separation between the binder and the active material particles and the aluminum foil; while the molecular chain of Comparative Example 1 (PVDF) is simple, and the interaction between it and the active material is mainly through the weak van der Waals force formed by F atoms and H atoms, so it is very easy to fall off from the pole piece; It can be seen from Example 1 and Comparative Example 2 that the sulfonated polyimide binder containing cyclodextrin has a stronger bonding ability, because there are multiple hydroxyl groups in the molecular structure of cyclodextrin, and these hydroxyl groups can form hydrogen bonds and other interactions with the surface of the electrode material to provide good bonding force;
[0110] As can be seen from Table 1, the impedance values of Examples 1-3 are generally larger than those of Examples 4-6. This is because the sulfonic acid groups of the sulfonated diamine monomers of Examples 1-3 are relatively few, and the sulfonic acid groups can dissociate into negatively charged sulfonate ions, thereby increasing the ionic conductivity in the electrode and reducing the electrode impedance.
[0111] As can be seen from Table 1, the first discharge specific capacity and capacity retention rate of Examples 1-6 are higher than those of Comparative Example 1, which shows that the electrochemical performance of the polyimide binder used in the present invention is better than that of commercial polyvinylidene fluoride;
[0112] From the attached Figure 3 and attached Figure 4 It can be seen that the polyimide binder in Example 1 uniformly coats the positive active material lithium cobalt oxide and the conductive carbon black, and the positive electrode components are closely connected to form a complete and tight conductive structure. The bonding performance of the positive electrode components is very strong, and the coating and bonding effects are good; while the active material of the electrode sheet made of the polyvinylidene fluoride binder in Comparative Example 1 is basically exposed on the surface, because the polyvinylidene fluoride binder and the active material only rely on the van der Waals force, and the bonding ability is poor;
[0113] The positive electrode sheets prepared in Example 1, Comparative Example 1 and Comparative Example 2 were assembled into button cells and subjected to charge and discharge cycle tests. The test results are shown in the attached Figure 7 As shown, after 200 cycles, the discharge specific capacity of the button cell assembled in Example 1 remains almost unchanged, and the capacity retention rate reaches 99%; after 200 cycles, the capacity of Comparative Examples 1 and 2 decays rapidly, and the discharge specific capacity of Comparative Example 2 is reduced to half of the original, and the discharge specific capacity of Comparative Example 1 is only 30% of the original. This shows that the electrode sheet prepared by the polyimide binder of the present invention is used in lithium-ion batteries, which can effectively improve the electrochemical performance of lithium-ion batteries.
[0114] In summary, the polyimide binder for the positive electrode of the lithium ion battery of the present invention uses polyimide as a skeleton, has excellent thermal stability, strong mechanical properties, improves the bonding strength of the binder, and effectively inhibits the detachment between the binder and the active material particles and the aluminum foil; the polyimide binder for the positive electrode of the lithium ion battery of the present invention includes cyclodextrin on the polyimide skeleton chain, and there are multiple hydroxyl groups in the molecular structure of cyclodextrin, and these hydroxyl groups can form hydrogen bonds and other interactions with the surface of the electrode material to provide good bonding force; the internal pore structure of cyclodextrin can also promote the penetration of electrolyte and ion migration, thereby improving the cycle performance; the polyimide binder for the positive electrode of the lithium ion battery of the present invention introduces groups such as sulfonate groups, which can dissociate sulfonate ions with negative charges, increase the ionic conductivity in the electrode, and improve the transmission efficiency of lithium ions in the electrode; the electrode sheet prepared by the polyimide binder obtained by the present invention is used in a lithium ion battery, which effectively enhances the electrochemical performance of the lithium ion battery.
[0115] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polyimide binder for a lithium ion battery positive electrode, characterized in that: The polyimide binder for the positive electrode of the lithium ion battery includes a polyimide containing cyclodextrin and a sulfonic acid group, and the polyimide structural formula is shown in structural formula 1: Wherein, m is any integer from 100 to 1000, and the weight average molecular weight is greater than 20000.
2. The polyimide binder for lithium ion battery positive electrode according to claim 1, characterized in that: The A group in the structural formula 1 is selected from any one of the following structural formulas:
3. The polyimide binder for lithium ion battery positive electrode according to claim 1, characterized in that: The B group in the structural formula 1 is selected from any one of the following structural formulas:
4. A method for preparing a polyimide binder for a lithium ion battery positive electrode, characterized in that: The steps include: (1) Under nitrogen protection, cyclodextrin, sulfonated diamine and triethylamine are dissolved in an organic solvent, stirred until fully dissolved, and then dibasic acid anhydride is added, and stirred at 60-100° C. for 6-12 hours to obtain a solution containing sulfonated polyamic acid included in cyclodextrin; (2) Add benzoic acid and a catalyst to the solution of sulfonated polyamic acid encapsulated by cyclodextrin obtained in step (1), raise the temperature to 180-220° C., react at a constant temperature for 10-18 hours, perform imidization, cool to room temperature, add a washing solvent to precipitate, filter, and obtain the polyimide binder for the positive electrode of a lithium ion battery.
5. The method for preparing a polyimide binder for a lithium ion battery positive electrode according to claim 4, characterized in that: In step (1), the molar ratio of the cyclodextrin to the sulfonated diamine is 1:0.5-1.5; the molar ratio of the sulfonic acid group in the sulfonated diamine to triethylamine is 1:0.9-1.1; The cyclodextrin is selected from one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin; The organic solvent is selected from one or a mixture of two or more of m-cresol, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, and p-chlorophenol; The solid content of the sulfonated polyamic acid solution is 10-25 wt %.
6. The method for preparing a polyimide binder for a lithium ion battery positive electrode according to claim 4, characterized in that: In step (2), the washing solvent is selected from one or more of ethyl acetate, methanol, ethanol, isopropanol, ethylene glycol, 2-butanol or cyclopentanol; The catalyst is selected from one of quinoline, isoquinoline or tertiary amine.
7. The polyimide binder for lithium ion battery positive electrode according to claim 1, characterized in that: The method for preparing the lithium ion battery positive electrode sheet with the polyimide binder for the lithium ion battery positive electrode comprises the following steps: S1, taking a polyimide binder and stirring it to dissolve it in a solvent to obtain a binder solution, grinding and mixing the positive electrode active material and the conductive agent, and then adding them to the binder solution, and adjusting the viscosity of the mixed material to 2000-10000 mPa·s by adding a solvent to obtain a black slurry; S2. The black slurry obtained in step S1 is evenly coated on aluminum foil, and compacted after drying to obtain a positive electrode sheet for a lithium-ion battery.
8. The polyimide binder for lithium ion battery positive electrode according to claim 7, characterized in that: In step S1, the solvent is selected from one of N,N-dimethylformamide, N,N-dimethylformamide or N-methylpyrrolidone; The positive electrode active material is selected from one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide or ternary positive electrode material nickel cobalt manganese oxide; The conductive agent is selected from one or more of acetylene black, superconducting carbon black Super P, carbon nanotubes, graphene and Ketjen black.
9. The polyimide binder for lithium ion battery positive electrode according to claim 7, characterized in that: In step S1, the mass concentration of the binder solution is 5%-20%; in step S2, the drying is vacuum drying at 80°C-120°C.
10. The polyimide binder for lithium ion battery positive electrode according to claim 7, characterized in that: In step S1, the positive electrode active material content is 2 mg cm -2 -4mg cm -2 ; In step S2, the positive electrode plate of the lithium-ion battery is composed of an active material layer and an aluminum foil; the active material layer is composed of a positive electrode active substance, a conductive agent and a polyimide binder; the mass content of the binder in the active material layer is 1%-15%; the mass content of the conductive agent in the active material layer is 2%-25%.
Citation Information
Patent Citations
Sulfonated polyimide binder, electrode plate and lithium ion battery
CN111777984A
Polyimide binder and negative plate
CN113555552A
Branched cross-linked polyamide acid solution, polyimide adhesive as well as preparation method and application of branched cross-linked polyamide acid solution and polyimide adhesive
CN114805804A
Polyimide flexible film based on cyclodextrin polyrotaxane and preparation method thereof
CN115806683A
Lithium-Ion Battery Conductive Bonding Agent and Production Method Thereof, Lithium-Ion Battery Electrode Plate and Production Method Thereof, and Lithium-Ion Battery
US20190081350A1
Cited By
Cross-linked polyimide binder for silicon-based negative electrode of lithium ion battery and preparation method of cross-linked polyimide binder
CN120442211A
Polyimide binder for positive electrode of lithium-ion battery and preparation method for polyimide binder
WO2026092040A1